Quality of Life in Young Adults With Cerebral Palsy: A Longitudinal Analysis of the SPARCLE Study - Vidart d'Egurbide Bagazgoïtia, Nicolas; Ehlinger, Virginie; Duffaut, Carine; Fauconnier, Jérôme; Schmidt-Schuchert, Silke; Thyen, Ute; Himmelmann, Kate; Marcelli, Marco; Arnaud, Catherine (Frontiers in Neurology, 2021)
Introduction: While most people with cerebral palsy (CP) will have a life expectancy similar to that of the general population, international research has primarily focused on childhood and adolescence, and knowledge about the quality of life (QoL) of young adults with CP, its trajectories and associated factors remains scarce. Methods: This longitudinal study included young adults with CP living in five European regions and who had previously participated in the SPARCLE cohort as children and/or adolescents. Their QoL in the Psychological well-being and Social relationships domains was estimated using age-appropriate validated instruments (KIDSCREEN-52 in childhood/adolescence, WHOQOL-Bref in young adulthood). We used generalized linear mixed-effect models with random intercept to estimate long-term trajectories of QoL in both domains, and to investigate whether severity of impairment, pain and seizure influenced these trajectories. We sought to identify potentially different trajectories of QoL from childhood to adulthood using a shape-based clustering method. Results: In total, 164 young adults with CP aged 22-27 years participated in the study. Psychological well-being linearly decreased by 0.78 points (scale 0-100) per year (95% confidence interval (CI) -0.99 to -0.56) from childhood to young adulthood, whereas QoL in the Social relationships domain increased (β coefficient 1.24, 95% CI 0.92 to 1.55). Severity of impairment was associated with reduced QoL in all life periods of the study (childhood, adolescence, young adulthood): motor impairment with Social relationships, and more nuancedly intellectual disability with Psychological well-being and Social relationships. At all periods, frequent pain significantly reduced Psychological well-being and seizures were associated with lower QoL in the Social relationships domain. In both domains, we identified a group of individuals with CP who presented a reverse trajectory compared with the general QoL trajectory. Conclusion: Identification of QoL trajectories and their associated factors yields improved knowledge about the experience of individuals with CP until young adulthood. Further studies are needed to better understand the determinants that have the greatest influence on the different shapes of long-term trajectories of QoL.